PENGARUH PEMBERIAN INSENTIF DAN PENGAWASAN TERHADAP KINERJA PERSONEL POLSEK PAMEKASAN KABUPATEN PAMEKASAN - jurnalmap map; Ach. Maulid Humaidi; Nugroho Mawardi Wibowo; Muninghar ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at Pamekasan Police Station in Pamekasan Regency with a total sample of 42 police officers. The objectives of this study are: 1) To describe the provision of incentives and supervision on the performance police officers, 2) To find out whether the provision of incentives and supervision has a simultaneous influence on the performance police officers, 3) To find out whether the provision of incentives and supervision has a partial effect on police officers, 4) To find out which variable among incentives and supervision has a dominant influence on the performance police officers. The results showed that: 1. Simultaneously, the provision of incentives and supervision simultaneously had a significant influence on the performance of Pamekasan police officers in Pamekasan Regency, 2. Partially, the provision of incentives and supervision partially has a significant influence on the performance of Pamekasan police officers in Pamekasan Regency. Keywords: Providing Incentives, Supervision and Performance of Personnel